Analisa Pengaruh Filler Serbuk Zinc Terhadap Sifat Mekanik Sambungan Beda Material Pada Las Titik Antara Baja Tahan Karat Dan Aluminium - nugroho, muhamad kholik fajar; , muhammad alfatih hendrawan .ST.MT (2017)
Availability of fossil fuels dwindling human demands for innovation in energy savings. An engine with high fuel efficiency is one solution to the energy savings that can be obtained by reducing vehicle weight. The type of material used will affect the weight of the vehicle. Stainless steel and aluminum is a material that can not be separated in the automotive industry. However, in the manufacturing process, the joiningbetween stainless steel and alumunium by welding is difficult because its melting point is much different. This study tried to determine the strength of welded joints different points using a filler material with or without filler.Research uses ferrite stainless steel 1 mm thick 430 series and 6019 series aluminum 1.2 mm thick zinc with as powder filler. Welding process using spot welding machine brands Dayok 0K-25 models. Specimens were divided into 2 groups: with filler and without filler with variations in current 6000 A, 7000 A and 8000 A. The time variation is 0.2 s; 0.3 s; and 0.4 s. Tests were conducted to determine the mechanical properties of welded joints that point shear testing (Tensil Shear Load ) and microhardness Vickers hardness testing. Shear testing using standard testing ASME IX. While the Vickers hardness testing using standard testing microhardness AWS D8.9-97.The results showed that the addition of zinc powder filler with a variety of current and time is not so significant effect on the weld joint. In contrast to the results of hardness test specimen in which an increasein violence that was significant at the weld joint areas compared to the parent metal. For optimum strength of welded joints on the specimen using zinc powder filler in the variation of the current 6000 A and 0.2 seconds with a value of 810,495N while for specimens without filler highest strength values at current variation 8000A and time of 0.4 seconds with a value of 869 , 27N. While the highest hardness values are also present in the area of the weld metal (nugget) specimens using a filler with a current of 8000 A and a time of 0.4 seconds